Pengembangan E-Modul Berbasis Pendektan Multipel Representasi untuk Meningkatkan Pemahaman Konsep Calon Guru Fisika di Masa Pandemi Covid-19 - Ahmad Busyairi; Ahmad Harjono; Aris Doyan; Sutrio Sutrio; I Wayan Gunada (Department of Physics Education, Universitas Mataram, 2021)
This study aims to develop a physics e-module based on a multiple representation approach to improve understanding of the concepts of prospective physics teachers on the kinematics of straight motion and parabolic motion. This type of research is research and development. The development stage in this study uses a 4-D model (Define, Design, Develop, Disseminate). The instruments used in this study consisted of; validation sheets, questionnaires, and concept understanding test instruments. Validation sheets are used to obtain assessments and suggestions for the initial product draft that was developed in terms of material, media, and language aspects. There are 3 experts involved in this validation. Based on the validation results, it shows that the initial draft of the e-module is feasible to use with a very good category for all aspects (material, media, and language). After going through the revision stage in accordance with the validator's suggestion, then a limited trial was carried out on 9 (nine) prospective physics teachers. Based on the results of the limited trial, it is shown that the module is feasible to proceed to a wider trial stage. The wider trial aims to determine the effectiveness of the use of e-modules in increasing the understanding of the concepts of prospective physics teachers. Based on the results of a wider trial, it shows that e-modules can improve understanding of concepts in the medium category with an N-gain score of 0.41. Thus, it can be concluded that the e-modules that have been developed are feasible and can be used as alternative learning to improve learning outcomes. understanding the concept of prospective physics teacher during the Covid-19 pandemic.